Implikasi Putusan Mahkamah Konstitusi Nomor 1/PHPU.PRES-XXII/2024 terhadap Pelaksanaan Pemilihan Kepala Daerah - Ristiawati, Risni; risadi, Rif’at madani; tiarridza, Dimas sis; Aeni, Azratul; Rianda, Zainal Muhammad; Hamzah, M Arfin (Banua Law Review, 2024)
The Constitutional Court's decision highlights the potential for government interference which could disrupt the independence of the KPU and Bawaslu in carrying out their duties. In addition, the decision also emphasizes the need for fundamental changes in election supervision arrangements to ensure honesty, fairness and integrity in the democratic process. The implications of the Constitutional Court's Decision Number 1/PHPU.PRES-XXII/2024 also open discussions about social assistance policies and the potential for politicization in the context of general elections. Regional Head Elections (Pilkada) are an important cornerstone of Indonesian democracy, but are often accompanied by legal and procedural controversies. The Constitutional Court (MK) Decision Number 1/PHPU.PRES-XXII/2024 is a crucial point, highlighting various aspects including the composition of the selection team, the role of Bawaslu, and the use of social assistance in a political context. This ruling questions the steps taken by related parties, the potential for government interference with the independence of institutions, and the need for fundamental changes in election supervision to ensure honesty, fairness and integrity. The implications of the Constitutional Court's decision open discussions about transparency, accountability, campaign regulations, and taking action against election violations, with the hope of strengthening integrity and justice in Indonesia's democratic system.